PENDAMPINGAN ANAK MILENIAL DALAM MEMBACA AL QUR’AN DENGAN METODE NEURO NADI ACEH - Andri Nirwana; Fahmi Arfan; Sayed Akhyar; Syardan Jalil (Prosiding Seminar Nasional USM, 2019)
The Iqra method has weaknesses in the dignity, short length of reading, the facts show that the alumni of this education are less considering the nature and meaning of letters. Weaknesses and weaknesses of the Iqra Method should be able to evaluate the method, as a solution to tackle the problem, the iqra method provides an opportunity to innovate for other methods. The Neuro Nadi Technique Method offers a 7-70 year old Nadi Quranic Learning Center program. A specialized work system of the neuro pulse method can focus the work of the left and right brain. Neuro Nadi Aceh (NNA) in research has competence in reading the Qur'an and giving better results than the previous Iqra methods. For this study the NNA institute was useful in teaching the Koran, referring to and then refining long-standing methods and the benefits of supporting Islamic Sharia in Aceh.